Foreign workers reduction in Malaysian construction industry - Wai, Fun Choong; Mohd Amir Shazwan, Hashim; Abdolreza, Toudehdehghan (INTI International University, 2018)
Foreign or migrant workers are the indispensable workforces that has become part of the lives and economy in Malaysia. However, the presence of rising number of illegal foreign workers and much higher percentage of unskilled foreign workers than that of skilled and semi skilled have undeniable induced negative impact on political, economic and social aspect. The objectives of this research is to identify the factors for reduction of foreign workers and to propose strategies for reduction of foreign workers in Malaysian construction industry. Data were collected through explanatory sequential mixed method. The questionnaires were sent to the construction professional that have direct contacts with foreign workers and are working in G7 construction firm. The three principal factors for reduction of foreign workers to the Malaysian construction industry are "Imposing of new policies", "Foreign workers' main objective is only to earn income" and "Reduced quality of work (Bad workmanship)". This research proposes that "Enhance safety practice and procedure", "Working condition improved machinery for machine operator" and "Industrialized Building Systems" as the strategies for reduction of foreign workers.